Efikasi Diri Pengambilan Keputusan Karir pada Masa Transisi Karir Mahasiswa Universitas Airlangga : Sebuah Studi Fenomenologi - Hanifa, Fadiya Dina; Fardana, Nur Ainy; Yoenanto, Nono Hery (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The career transition from undergraduate studies to the world of work is a very important step in career planning. During this transition period, career counseling is needed in assisting undergraduate students to achieve academic success and career readiness as has been written in several educational reforms such as the Blueprint for Reform from the US Department of Education in 2010 and No Child Left Behind in 2001 (Li, Mau, and Bray, 2017). One aspect that can affect career readiness is Career Decision-Making Self Efficacy (CDSE). This study aims to see the description of Career Decision-Making Self Efficacy of students in the career transition period. Counseling data was processed using a qualitative descriptive phenomenology method to see the meaning of undergraduate students in their Career Decision-Making Self Efficacy. The results of the study that showed a description of students' Career Decision-Making Self Efficacy are expected to be taken into consideration for holding activities aimed at improving students' Career Decision-Making Self Efficacy in the future.